Epstein-Barr Virus BART Long Non-coding RNAs Function as Epigenetic Modulators in Nasopharyngeal Carcinoma - Verhoeven, Rob J. A.; Tong, Shuang; Mok, Bobo Wing-Yee; Liu, Jiayan; He, Songtao; Zong, Jingfeng; Chen, Yixin; Tsao, Sai-Wah; Lung, Maria Li; Chen, Honglin (Frontiers in Oncology, 2019)
Epstein-Barr virus (EBV) establishes lifelong latent infection in humans and is associated with several lymphoid and epithelial cancers. In nasopharyngeal carcinoma (NPC), EBV expresses few viral proteins but elevated levels of BART RNA, which includes viral microRNAs and long non-coding RNAs (lncRNAs). BART lncRNAs localize within the nucleus of EBV-infected cells and knockdown of BART lncRNAs significantly affects the expression of genes associated with cell adhesion, oxidoreductase activity, inflammation and immunity. Notably, downregulation of IKAROS family zinc finger 3 (IKZF3/Aiolos), which plays a role in lymphocyte development and cell attachment, occurred in NPC C666-1 cells following BART lncRNA-knockdown. Since Aiolos expression is normally restricted to lymphoid cells and rarely observed in epithelial cells, induction of Aiolos by BART lncRNA was confirmed by expressing the major BART lncRNA isoform, RPMS1, in EBV-positive and -negative cells. BART lncRNA associated with the CBP/p300 complex and RNA polymerase II (Pol II) in the nucleus, suggesting that BART lncRNAs may mediate epigenetic regulation of gene expression through interaction with the chromatin remodeling machinery. This contention is further supported by evidence that BART lncRNA appears to stall Pol II at the promoter region and may regulate IFNB1 and CXCL8 expression by inhibiting transcription by Pol II in NPC. We hypothesise that EBV BART lncRNA expression modulates host gene expression and maintains EBV latency by interfering with histone methylation and acetylation processes. Aberrant expression of affected host genes mediated by BART lncRNA may lead to immune evasion, progression and metastasis of NPC.